Reducing asthma attacks in disadvantaged school children with asthma: study protocol for a type 2 hybrid implementation-effectiveness trial (Better Asthma Control for Kids, BACK) - Huebschmann, Amy G.; Wagner, Nicole M.; Gleason, Melanie; Brinton, John T.; Brtnikova, Michaela; Brewer, Sarah E.; Begum, Anowara; Armstrong, Rachel; DeCamp, Lisa Ross; McFarlane, Arthur; DeKeyser, Heather; Coleman, Holly; et al. (Implementation science : IS, 2024)
Background Asthma is a leading cause of children’s hospitalizations, emergency department visits, and missed school days. Our school-based asthma intervention has reduced asthma exacerbations for children experiencing health disparities in the Denver Metropolitan Area, due partly to addressing care coordination for asthma and social determinants of health (SDOH), such as access to healthcare and medications. Limited dissemination of school-based asthma programs has occurred in other metropolitan and rural areas of Colorado. We formed and engaged community advisory boards in socioeconomically diverse regions of Colorado to develop two implementation strategy packages for delivering our school-based asthma intervention — now termed “Better Asthma Control for Kids (BACK)" — with tailoring to regional priorities, needs and resources. Methods In this proposed type 2 hybrid implementation-effectiveness trial, where the primary goal is equitable reach to families to reduce asthma disparities, we will compare two different packages of implementation strategies to deliver BACK across four Colorado regions. The two implementation packages to be compared are: 1) standard set of implementation strategies including Tailor and Adapt to context, Facilitation and Training termed, BACK-Standard (BACK-S); 2) BACK-S plus an enhanced implementation strategy, that incorporates network weaving with community partners and consumer engagement with school families, termed BACK-Enhanced (BACK-E). Our evaluation will be guided by the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework, including its Pragmatic Robust Implementation Sustainability Model (PRISM) determinants of implementation outcomes. Our central hypothesis is that our BACK-E implementation strategy will have significantly greater reach to eligible children/families than BACK-S (primary outcome) and that both BACK-E and BACK-S groups will have significantly reduced asthma exacerbation rates (“attacks”) and improved asthma control as compared to usual care. Discussion We expect both the BACK-S and BACK-E strategy packages will accelerate dissemination of our BACK program across the state – the comparative impact of BACK-S vs. BACK-E on reach and other RE-AIM outcomes may inform strategy selection for scaling BACK and other effective school-based programs to address chronic illness disparities. Trial registration Clinicaltrials.gov identifier: NCT06003569, registered on August 22, 2023, https://classic.clinicaltrials.gov/ct2/show/NCT06003569 .